CCNP and CCIE Enterprise Core & CCNP Advanced Routing Portable Command Guide : All ENCOR (350-401) and ENARSI (300-410) Commands in One Compact, Portable Resource - Empson, Scott; Gargano, Patrick (Cisco Press, 2020)
All ENCOR (350-401) and ENARSI (300-410) Commands in One Compact, Portable Resource Use this fully updated quick reference resource to help memorize commands and concepts as you earn your CCNP or CCIE certification. Filled with valuable, easy-to-access information, it's portable enough to use anywhere. This guide summarizes all Cisco IOS software commands, keywords, command arguments, and associated prompts associated with the CCNP and CCIE Enterprise Core (ENCOR 350-401) and CCNP Enterprise Advanced Routing and Services (ENARSI 300-410) certification exams. Tips and examples help you apply commands to real-world scenarios, and configuration samples show their use in network designs. Coverage includes: Layer 2: VLANs, STP, Inter-VLAN Routing Layer 3: EIGRP, OSPF, Redistribution, Path Control, BGP Infrastructure Services and Management Infrastructure Security Network Assurance Wireless Security and Troubleshooting Overlays and Virtualization This Portable Command Guide provides: Logical how-to topic groupings for a one-stop resource Great for review before your ENCOR 350-401 and ENARSI 300-410 certification exams Compact size makes it easy to carry with you wherever you go "Create Your Own Journal" section with blank, lined pages enables you to personalize the book for your needs This book is part of the Cisco Press Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco certification exams. Titles in the Cisco Press Certification Self-Study Product Family are part of a recommended learning program from Cisco that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press